2022
DOI: 10.1093/cid/ciac531
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patient With Hemorrhagic Meningitis Associated With Inhalation Anthrax

Abstract: This report describes a 49-year-old male construction worker who acquired a Bacillus anthracis infection after working on a sheep farm. He experienced a severe respiratory infection, septic shock, and hemorrhagic meningoencephalitis with severe intracranial hypertension. After several weeks with multiple organ dysfunction syndrome, he responded favorably to antibiotic treatment. Three weeks into his hospitalization, an intracranial hemorrhage and cerebral edema led to an abrupt deterioration in his neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The key to effectively managing inhalational anthrax appears to be the prompt introduction of antibiotics and vigorous supportive care [121]. Other techniques, such as chest tube drainage for recurrent hemorrhagic pleural effusions, can result in good clinical improvement [122].…”
Section: Treatmentmentioning
confidence: 99%
“…The key to effectively managing inhalational anthrax appears to be the prompt introduction of antibiotics and vigorous supportive care [121]. Other techniques, such as chest tube drainage for recurrent hemorrhagic pleural effusions, can result in good clinical improvement [122].…”
Section: Treatmentmentioning
confidence: 99%
“…The meeting attendees listened to presentations on anthrax clinical features (38), optimal antimicrobial drug treatment and PEP from both an efficacy (in vitro, in vivo, and observational clinical data) and safety standpoint (34,35,39,42,46,47), the value and use of antitoxins (37,39,(48)(49)(50), and methods to rapidly identify and optimally treat anthrax meningitis (39)(40)(41)51,52). The attendees then provided individual expert opinions on proposed edits to previous antimicrobial drug and antitoxin PEP and treatment guidelines.…”
Section: Review Of the Evidencementioning
confidence: 99%
“…However, patients who received mannitol had higher odds of survival than those who did not (OR = 24.00; 95% CI = 1.66-347.85). For example, two of the rare survivors of anthrax meningitis received mannitol or mannitol with hyperosmolar therapy (49,97). In addition, bacterial meningitis studies in animal models found that 3% hypertonic saline reduces intracranial pressure, improves cerebral perfusion pressure, inhibits aquaporin-4 expression, reduces cerebral edema, and attenuates neuronal injury.…”
Section: Cerebral Edema In Anthrax Meningitismentioning
confidence: 99%